Design and Numerical Investigation on Octagonal Barge-Type FOWT with Counterweight Suspension System - Yung-Chun Sun; Ray-Yeng Yang (Energies)
This study aims at enhancing platform design and passive control technology, reducing maintenance costs, and increasing stability and efficiency. The selected site for this study is offshore water in Hsinchu, Taiwan. Owing to shallow water conditions at the selected site, an octagonal barge-type platform was chosen for investigation of its suitability in this study. A counterweight suspension system was used to improve stability and avoid pitch resonance. Meanwhile, an octagonal barge platform carrying the NREL-5MW offshore wind turbine was designed. It uses SolidWorks for modeling, Ansys AQWA for hydrodynamic calculations, and Orcina OrcaFlex for wind/wave/current coupling dynamic analysis. Key research results include optimizing the counterweight suspension system and ensuring compliance with Det Norske Veritas (DNV) regulations, covering Ultimate Limit States (ULSs), Accidental Limit States (ALS)s, Serviceability Limit States (SLSs), and Fatigue Limit States (FLSs). Thus, the major inspections include platform motions, mooring line tension, and suspension system tension during turbine operation and parking. Comparisons are made with and without the counterweight suspension system.